Diabetic retinopathy detection and classification by using deep learning - Hossain, Shahriar; Evan, Md. Nurusshafi; Farhin, Fariya Zakir; Nabil, Mashrur Karim; Sadman, Sameen (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.